Enzymatic synthesis of fructooligosaccharides from sucrose by endo-inulinase-catalyzed transfructosylation reaction in biphasic systems. (June 2018) - Karboune, Salwa; Appanah, Neeyal; Khodaei, Nastaran; Tian, Feng
Graphical abstract: Highlights: Production of fructooligosaccharides (FOSs) by endo-inulinase-catalyzed transfructosylation was studied in biphasic systems. The highest FOS yield was obtained in butyl acetate/buffer biphasic system with nystose being the main end-product. Interaction between reaction time and solvent proportion had the most significant effect on FOS yield. 66°Bx and 15°Bx maple syrup based-biphasic system favored production of nystose/fructosyl-nystose and kestose, respectively. Abstract: The biocatalytic approach based on the endo-inulinase-catalyzed transfructosylation reaction of sucrose in organic solvent/buffer biphasic reaction systems was investigated for the synthesis of fructooligosaccharides (FOSs). Combining kinetics and end-product profiling contributed to the understanding of the reaction selectivity and to the identification of the best biphasic system. Indeed, the highest FOS bioconversion yield (60.2%) was obtained in butyl acetate/buffer system, with nystose being the main end-product. The effects of the reaction parameters were studied using response surface methodology. Enzyme unit exhibited the most significant linear effect in the kestose concentration model, whereas the reaction time was the most significant parameter in the nystose concentration model. However, in the fructosyl-nystose concentration model, all linear terms exerted significant effects. Among the interactive effects, the interaction between reaction time and solvent proportion had the most significant effect on the kestose and nystose concentrations and on the bioconversion yield of FOS. The developed models are expected to provide the capability to FOS with targeted composition. FOS production by endo-inulinase was investigated in maple syrup-based biphasic media. The highest production of kestose was obtained using maple syrup 15°Bx, whereas the 66°Bx maple syrup resulted in the highest productions of nystose and fructosyl-nystose.